Growth challenges and recovery in 1247 children with congenital diaphragmatic hernia: a 10-year follow-up - Jordan, Alexander; Mohr, Christoph; Martel, Richard; Zahn, Katrin; Schaible, Thomas; Adam, Rüdiger; Boettcher, Michael; Elrod, Julia (European journal of pediatrics, 2025)
Growth abnormalities in children with congenital diaphragmatic hernia (CDH) are a significant concern for long-term developmental outcomes. To explore growth in this population, the evolution of weight, height, body mass index (BMI), and head circumference as vital indicators of growth and developmental progress in CDH survivors were investigated. We analyzed 1247 CDH patients treated at our center from 2000 to 2022. Growth trends regarding weight, height, BMI, and head circumference of surviving patients without major comorbidities were compared with standard pediatric growth milestones for term and preterm children. Factors associated with growth disparities were assessed. A total of 835 CDH survivors without major comorbidities were identified who exhibited notably slower weight gain, which stabilized at a reduced level beyond the age of 2 years. By 6 years of age, height normalized in term-born children, while head circumference normalized at 1 year of age. BMI remained low throughout childhood. Defect size and gestational age were important independent predictors of growth restriction, whereas ECMO therapy was not an independent risk factor for low weight or small stature. Preterm children tended to exhibit lower growth percentiles and delayed catch-up.
Online veröffentlicht: 7. November 2025
Gesehen am 11.12.2025